11, 11, 12, 12‐Tetracyanonaphtho‐2, 6‐quinodimethane in Contact with Ferromagnetic Electrodes for Organic Spintronics. (31st May 2018) - Shi, Shengwei; Sun, Zhengyi; Liu, Xianjie; Bedoya‐Pinto, Amilcar; Graziosi, Patrizio; Yu, Huangzhong; Li, Wenting; Liu, Gang; Hueso, Luis; Dediu, Valentin A.; Fahlman, Mats
Abstract: Spinterface engineering has shown quite important roles in organic spintronics as it can improve spin injection or extraction. In this study, 11, 11, 12, 12‐tetracyanonaptho‐2, 6‐quinodimethane (TNAP) is introduced as an interfacial layer for a prototype interface of Fe/TNAP. An element‐specific investigation of the electronic and magnetic structures of Fe/TNAP system by use of near edge X‐Ray absorption fine structure (NEXAFS) and X‐ray magnetic circular dichroism (XMCD) is reported. Strong hybridization between TNAP and Fe and induced magnetization of N atoms in TNAP molecule are observed. XMCD sum rule analysis demonstrates that the adsorption of TNAP reduces the spin moment of Fe by 12%. In addition, induced magnetization in N K‐edge of TNAP is also found with other commonly used ferromagnets in organic spintronics, such as La0.7 Sr0.3 MnO3 and permalloy, which makes TNAP a very promising molecule for spinterface engineering in organic spintronics. Abstract : 11, 11, 12, 12‐tetracyanonaptho‐2, 6‐quinodimethane (TNAP) is introduced as an interfacial layer in organic spintronics . The electronic and magnetic structures at ferromagnetic (FM)–TNAP interfaces are investigated, which demonstrates the key importance of the spinterface properties for the realization of organic spintronic devices with the required parameters. The results show promising application of TNAP to modify the spinterface in real spintronic devices.